PENGEMBANGAN MEDIA PEMBELAJARAN JOBSHEET UNTUK MATA PELAJARAN ADMINISTRASI INFRASTRUKTUR JARINGAN DI SMK NEGERI 1 NGAWI - Putra, Fatrah Ahmad; Marpanaji, Eko (Department of Electronics and Informatics Engineering Education, 2024)
This research goals is: (1) Develop jobsheets for the network infrastructure administration subject at SMK Negeri 1 Ngawi; and (2) assess the feasibility of the jobsheets for the network infrastructure administration subject at SMK Negeri 1 Ngawi. This is a Research & Development (R&D) implementing the ADDIE model, with several steps such as analysis, design, development, implementation, and evaluation. The outcome product is jobsheets as learning media for the Network Infrastructure Administration subject. The research targets 11th-grade students majoring in Computer and Network Engineering at SMK Negeri 1 Ngawi. The product will be evaluate and assessed by validators in both material content and media, who are lecturers from the Department of Electronic and Informatics Engineering Education, Faculty of Engineering, Yogyakarta State University (UNY). Additionally, it will be assessed through questionnaires filled out by students. The results of this research showing that: (1) The developed product, which is jobsheets as learning media, categorized as feasible with an very good assessment from both material content and media validators; (2) Overall aspects in the development of jobsheets as learning media have achieved a very high level and are categorized as